2021
DOI: 10.1016/j.jksus.2020.101262
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being during COVID-19 lockdown: Insights from a Saudi State University’s Academic Community

Abstract: Objectives Measures to control the on-going Covid-19 pandemic such as quarantine and social distancing, together with information overload about the sporadic spread of the disease have negatively impacted many individuals’ mental and psychosocial health. This study aimed to investigate the prevalence of self-reported mental health parameters and the coping mechanisms of employees and students in a Saudi State University. Methods An online survey in both Arabic and Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 39 publications
2
56
0
1
Order By: Relevance
“…Self-reported deteriorations in student mental health, presenting as augmented psychological stress, anxiety, depression and even post-traumatic stress disorder, 20,63 appears to be a global phenomenon. 5,27,35,[64][65][66][67][68][69][70][71][72] In common with the general population, isolation, loneliness and worries about catching the disease have been found to be drivers of poor psychological health. 5,73 Specifically for students, the emergency transition to online learning has had mixed satisfaction outcomes and has found to be a stressor, particularly when associated with increased workloads and where learning technologies or internet connectivity are inadequate.…”
Section: Covid-19 Impacts On Student Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-reported deteriorations in student mental health, presenting as augmented psychological stress, anxiety, depression and even post-traumatic stress disorder, 20,63 appears to be a global phenomenon. 5,27,35,[64][65][66][67][68][69][70][71][72] In common with the general population, isolation, loneliness and worries about catching the disease have been found to be drivers of poor psychological health. 5,73 Specifically for students, the emergency transition to online learning has had mixed satisfaction outcomes and has found to be a stressor, particularly when associated with increased workloads and where learning technologies or internet connectivity are inadequate.…”
Section: Covid-19 Impacts On Student Mental Healthmentioning
confidence: 99%
“…27,33,[74][75][76] The vulnerability of family members to Covid-19 infection has also emerged as a source of worry for many students. 73 Familial support networks represent an important source of psychological support for students 67,70 and bereavement or serious illness affecting relatives, or indeed the fear of such events happening 77 have been a significant cause of poor mental health in 2020. 66 However, this is not always a straightforward positive relationship and at least one study has found that for a small proportion of students, increased family conflicts during lockdown have negatively affected their mental well-being.…”
Section: Covid-19 Impacts On Student Mental Healthmentioning
confidence: 99%
“…Articles also suggest that quarantined children 169 , adolescents 170 , university students [171][172][173][174] and adults 175 , mothers of young children 176 , and other healthy adults suffered from symptoms of poor mental health, such as post-traumatic stress, anger, and confusion 177,178 . One study in Turkey found a difference in the self-reported quality of life (better) of children as opposed to the perception of their parents 179 .…”
Section: Stressmentioning
confidence: 99%
“…Most of the COVID-19 studies in Saudi Arabia have focused on pre-existing conditions with final outcomes 20 , 21 , as well as dietary changes and mental health 22 , 23 . Given that lockdowns primarily promote a more sedentary and passive lifestyle, the present study aimed to determine the extent of altered lifestyle behavior changes during this period through a structured online survey distributed to residents of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%